1999
DOI: 10.1039/a906501f
|View full text |Cite
|
Sign up to set email alerts
|

Hemispherical synthesis of dendritic poly(L-lysine) combining sixteen free-base porphyrins and sixteen zinc porphyrins

Abstract: Dendritic poly(l-lysine) combining sixteen free-base porphyrins and sixteen zinc porphyrins hemispherically at the fifth generation was successfully synthesised and showed intramolecular fluorescence energy transfer in DMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…A poly(L-lysine) dendrimer that carries 16 free-base porphyrins in one hemisphere and 16 zinc porphyrins in the other one has been synthesized and studied in DMF solution [48]. In such a dendrimer, energy transfer from the Zn-porphyrin units to the free-base ones has been observed to occur with 43% efficiency.…”
Section: Dendrimersmentioning
confidence: 99%
“…A poly(L-lysine) dendrimer that carries 16 free-base porphyrins in one hemisphere and 16 zinc porphyrins in the other one has been synthesized and studied in DMF solution [48]. In such a dendrimer, energy transfer from the Zn-porphyrin units to the free-base ones has been observed to occur with 43% efficiency.…”
Section: Dendrimersmentioning
confidence: 99%
“…This prompted the synthesis of dendritic poly( L ‐lysine) 12 , which bears two hemispherically segregated domains comprised of 16 free‐base porphyrin (P FB ) units and 16 zinc porphyrin (P Zn ) units on the exterior surface. A steady‐state fluorescence study has shown the occurrence of a two‐dimensional P Zn ‐to‐P FB energy transfer with a Φ ENT value of 43 % 30. Here, photoexcitation of a certain P Zn unit in compound 12 is followed by an energy migration within the P Zn domain, and then the excitation energy is transferred to a P FB unit at a boundary of the two domains.…”
Section: Dendritic Light‐harvesting Antennaementioning
confidence: 99%
“…Dendrimers containing photoactive units [7][8][9][10][11][12][13][14][15][16][17] are particularly interesting for two reasons: (1) cooperation among the photoactive components can allow the dendrimer to perform specific functions, and (2) changes in the properties of photoactive components can be exploited to monitor the participation of dendrimers in chemical processes.…”
Section: -6mentioning
confidence: 99%